Designing WLAN Network-Based Mail Server Using MDAEMON - Michel Junior Sagala; Sapri Sapri; Eko Prasetyo Rohmawan (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
PT. Marketing Sakti Perumahan Syariah Bengkulu Branch is a company engaged in the residential property sector. So far, the company does not have its own mail server that is used to send and receive emails internally within the scope of the company, therefore difficulties in providing information to every employee who is in the same network at PT. Marketing Sakti Perumahan Syariah. In the process of sending email, it is managed by a computer as a mail server by distributing incoming email and sending it to members who are registered on the mail server. WLan network-based mail server using MDaemon is done offline at PT. Marketing Sakti Perumahan Syariah. The process of sending e-mails is managed by a computer known as a mail server by distributing incoming e-mails and then sending them to members who are registered on the mail server. Based on the tests that have been carried out, the Mail Server that has been built is running well as expected, where registered users can send emails to other registered users and display the contents of incoming emails through the in